Gathering dark - Fox, Candice (Forge, 2021)
"A convicted killer. A gifted thief. A vicious ganglord. A disillusioned cop. Together they're a missing girl's only hope. Dr. Blair Harbour, once a wealthy, respected pediatric surgeon, is now an ex-con down on her luck. She's determined to keep her nose clean and win back custody of her son. But when her former cellmate begs for help to find her missing daughter, Blair is compelled to put her new-found freedom on the line. Detective Jessica Sanchez has always had a difficult relationship with the LAPD. And her inheritance of a multi-million dollar mansion as a reward for catching a killer has just made her police enemy number one. It's been ten years since Jessica arrested Blair for cold-blooded murder. So when Jessica opens the door to the disgraced doctor late one night she expects abuse, maybe even violence. What comes next is a plea for help..."--